A comparative study of the accurate image reproduction of conventional film-based radiographs and digital radiographs an in vitro study - Cornejo, Daisy S.; Domingo, Pia Kristina B.; Ramos, Tristan Nathaniel C. (Adviser).
Radiographs have been used to detect and define the type and extent of disease in clinical situations. Primary importance is placed on their ability to reproduce accurate images of the structures under radiographic examination. The aim of this study was to compare the diagnostic accuracy of the image reproduction of both conventional and digital radiographs. Eight tooth specimens mounted in wax blocks were radiographically exposed under conventional and digital means. The images on the radiographs were then measured and compared to the actual measurement of each specimen. The t-test for equality of means was used to determine the statistical difference between both systems. The results of the study showed that the digital images were closer to the actual measurements of the specimens. Analysis showed that the difference between the diagnostic accuracy of images reproduced by conventional and digital means were statistically significant. Digital radiographs were more accurate than conventional radiographs in terms of an object's apico-coronal dimension.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Radiography, Dental; Radiography, Dental, Digital -- Methods